GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

Effects of dietary protein concentration on growth and anti-oxidant capacity of coho salmon Oncorhynchus kisutch (Walbaum, 1792) alevins - Cong-mei Xu; Hai-rui Yu; Qin Zhang; Ling-yao Li; Jing-jing Fan; Meng-jie Guo; Fang-hui Li; Xiang-yi Qiu; Ling-ling Shan (Aquaculture International, 2022)

Yield responses of four common potato cultivars to an industry standard and alternative rotation in Atlantic Canada - Mohammad Amir Azimi; Yefang Jiang; Fan-Rui Meng; Kang Liang (American Journal of Potato Research, 2022)
This study was conducted to evaluate yield responses of four potato ( Solanum tuberosum L.) cultivars (‘Russet Burbank’, ‘Shepody’, ‘Gold Rush’, and ‘Russet Prospect’) and soil N dynamic changes to two 3-year rotations in Prince Edward Island, Canada. The two rotations were the local industry standard potato–barley ( Hordeum vulgare L. )–red clover ( Trifolium pratense L.) rotation (PBC) and an alternative potato–soybean ( Glycine max L.)–barley rotation (PSB). All potato cultivars received 170 kg N ha − 1 input at planting without irrigation. Soil mineral N content before potato planting was significantly higher under the PBC rotation. However, the PBC rotation produced significantly lower yields, suggesting the possibility of excessive N supply from the plowed-down red clover. While cultivar and the interaction between cultivar and rotation did not show a significant difference in yield, yields of all cultivars were positively affected by the PSB rotation. The Gold Rush cultivar was affected the most (36%), followed by Russet Burbank (17%) and Prospect (14%) cultivars, with Shepody being the least affected (3%) by the alternative PSB rotation. Russet Burbank was the highest yielding cultivar under both rotations. With the three russet cultivars combined as a single russet cultivar, the PSB rotation significantly increased tuber yields, while the Shepody cultivar did not significantly benefit from the PSB rotation, suggesting that the russet cultivars responded more sensitively to the alternative rotation. Results demonstrate that adequately accounting for N supply from a preceding green manure crop is required for sustainable potato production in this humid temperate region.